Retrieval practice facilitates learning by strengthening processing in both the anterior and posterior hippocampus. Issue 1 (22nd October 2020) - Wiklund‐Hörnqvist, Carola; Stillesjö, Sara; Andersson, Micael; Jonsson, Bert; Nyberg, Lars
Abstract: Introduction and Methods: A large number of behavioral studies show that retrieval practice is a powerful way of strengthening learning of new information. Repeated retrieval might support long‐term retention in a quantitative sense by inducing stronger episodic representations or in a qualitative sense by contributing to the formation of more gist‐like representations. Here we used fMRI to examine the brain bases related to the learning effects following retrieval practice and provide imaging support for both views by showing increased activation of anterior and posterior hippocampus regions during a delayed memory test. Results: Brain activity in the posterior hippocampus increased linearly as a function of number of successful retrievals during initial learning, whereas anterior hippocampus activity was restricted to items retrieved many but not few times during the learning phase. Conclusion: Taken together, these findings indicate that retrieval practice strengthens subsequent retention via "dual action" in the anterior and posterior hippocampus, possibly reflecting coding of individual experiences as well as integration and generalization across multiple experiences. Our findings are of educational significance by providing insight into the brain bases of a learning method of applied relevance. Abstract : The hippocampus (HC) and the "testing effect" have each been studied extensively for their potential in memory and learning. Here we provide novel evidence related to the well‐established "testing effect" by highlighting that retrieval practice facilitates learning by strengthening processing in both the anterior and posterior HC. These findings are of educational significance by providing unique insights into the brain bases of a learning method of applied relevance and emphasize the important role of hippocampus for durable learning in school.